(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Early metabolic alterations often develop silently in young adults and may remain undetected until clinically significant disorders emerge. Changes in body composition, particularly the distribution of fat and lean mass, play a crucial role in metabolic regulation and long-term health outcomes. From a biophysical perspective, bioimpedance analysis provides a non-invasive method for evaluating tissue composition and functional metabolic risk. This study explores bioimpedance-based biophysical assessment of body composition as an indicator of metabolic risk in young adults. Electrical impedance parameters were analyzed to characterize body composition patterns and their association with metabolic vulnerability. Emphasis was placed on functional interpretation of impedance-derived indices rather than isolated anthropometric measures. The analysis revealed distinct body composition profiles associated with increased metabolic risk, even in individuals without overt clinical symptoms. The findings suggest that bioimpedance-based biophysical assessment offers valuable insight into early metabolic alterations. Application of this approach may support preventive screening strategies and early identification of metabolic risk in young adult populations.